2002
DOI: 10.1086/322999
|View full text |Cite
|
Sign up to set email alerts
|

The Organic Refractory Material in the Diffuse Interstellar Medium: Mid‐Infrared Spectroscopic Constraints

Abstract: This is an analysis of the 4000È1000 cm~1 (2.5È10 km) region of the spectrum of di †use interstellar medium (DISM) dust compared with the spectra of 13 materials produced in the laboratory which serve as analogs to the interstellar material. The organic signatures of extragalactic dust, carbonaceous chondritic material, and E. coli bacteria are also presented because these have been discussed in the literature as relevant to the di †use interstellar medium. Spectral analysis of the DISM allows us to place sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
411
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 342 publications
(436 citation statements)
references
References 79 publications
24
411
0
1
Order By: Relevance
“…It should also be noted that the primary reactant beam also contains carbon atoms as well as dicarbon and tricarbon molecules. Previous studies showed that tricarbon molecules have a significant entrance barrier upon reacting with benzene of more than 90 kJ mol -1 ; 57 therefore, under our experimental conditions, tricarbon does not react with benzene-d 6 . The lighter carbon (12 amu) and dicarbon reactants (24 amu) react with benzene-d 6 ; 58,59 due to the heavier ethynyl-d 1 radical (26 amu), carbon and dicarbon reactions lead only to products, which are lower in mass by 2 and 14 amu compared to those formed in the reaction of ethynyl-d 1 radicals with benzene-d 6 .…”
Section: Experimental and Data Analysismentioning
confidence: 69%
See 4 more Smart Citations
“…It should also be noted that the primary reactant beam also contains carbon atoms as well as dicarbon and tricarbon molecules. Previous studies showed that tricarbon molecules have a significant entrance barrier upon reacting with benzene of more than 90 kJ mol -1 ; 57 therefore, under our experimental conditions, tricarbon does not react with benzene-d 6 . The lighter carbon (12 amu) and dicarbon reactants (24 amu) react with benzene-d 6 ; 58,59 due to the heavier ethynyl-d 1 radical (26 amu), carbon and dicarbon reactions lead only to products, which are lower in mass by 2 and 14 amu compared to those formed in the reaction of ethynyl-d 1 radicals with benzene-d 6 .…”
Section: Experimental and Data Analysismentioning
confidence: 69%
“…This experiment was compared with a novel electronic structure calculation on the singlet C 8 D 7 surface. Phenylacetylene-d 6 is the primary product formed via indirect reactive scattering dynamics through a longlived reaction intermediate initiated by a barrierless addition of the ethynyl-d 1 radical to benzene-d 6 . This initial intermediate was found to decompose via a tight exit transition state located about 42 kJ mol -1 above the separated products; here, the deuterium atom is ejected almost perpendicularly to the rotational plane of the decomposing intermediate and almost parallel to the total angular momentum vector.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations